Assessment of knowledge, attitude, and practice related to brucellosis among livestock farmers and meat handlers in Saudi Arabia - Alghafeer, Mohammed H.; Aldhukair, Ebrahim F.; Alzahrani, Abdullah H.; Alsaedi, Abdullah S.; Almutairi, Omar N.; Aloliky, Abdulsalam A.; Almutairi, Masaad Saeed; Thabit, Abrar K. (Frontiers in Veterinary Science, 2024)
Background Brucellosis is a bacterial zoonotic infection that is endemic in Saudi Arabia and associated with clinical and economic impacts. Several studies from countries endemic for brucellosis evaluated the knowledge and attitude of livestock farmers regarding brucellosis. However, no such study was conducted in Saudi Arabia. This study aimed to evaluate the knowledge, attitude, and practice of livestock farmers and meat handlers in Saudi Arabia. Methods This was a cross-sectional questionnaire-based study, where participants were interviewed in-person in Arabic in livestock markets between September–December 2023. Convenient sampling was utilized. The questionnaire included basic demographics and questions to assess the knowledge, attitude, and practice toward personal protection and protection of the animals from brucellosis. The questionnaire was adapted from a previously validated survey and included 59 questions. Providing at least one correct answer to a certain question indicated a good knowledge about this item or a safe practice. The participants were divided into: farmers (shepherds working for the animal owners), commercial animal owners (those who rent a stockyard in the livestock market and employ farmers to sell their animals), and private animal owners (owners of private farms from which they sell their animals). Results 545 participants were interviewed (n = 291 farmers, n = 118 commercial animal owners, n = 113 private animal owners, and n = 23 animal slaughterhouse workers). >90% have heard of brucellosis. Lack of education and short experience (<5 years) of working with livestock were negatively associated with good knowledge of brucellosis symptoms and transmission (OR, 0.30; 95%CI, 0.10–0.94; p = 0.038 and OR, 0.23; 95%CI, 0.08–0.62; p = 0.004, respectively). Taking sick animals to the veterinarian was reported by 61.2%, whereas 36.4% follow safe practices when disposing of aborted fetuses. While 34% consume raw milk, only 10% consume rare/medium-rare meat. 51.2% acknowledged the need for more information on brucellosis. Conclusion This study revealed the need to augment the knowledge of people working with animals, particularly those with no school education and those with short work experience, via providing educational visits or materials or through veterinarians. This should help them identify human and animal brucellosis symptoms and increase the knowledge on how to protect oneself and animals from this disease.